Investigating the Possible Association between Toxoplasma gondii Infection and Multiple Sclerosis using a Combination of Serological and MRI Indices - Hijjawi, Nawal Sameeh; Al-Radaideh, Ali; El-Haj, Nawal (Jordan Medical Journal, 2025)
Background: The present study was established to investigate if there is any association between multiple sclerosis (MS) and toxoplasmosis using a combination of serological and MRI indices. Methods: 100 relapsing-remitting MS (RRMS) patients were recruited in the present study from the neurology clinic at Al-Bashir Hospital along with 34 age-matched healthy controls (HCs). MS patients as well as controls were tested for the presence of Toxoplasma IgG and IgM antibodies using ELISA technique. Magnetic resonance imaging (MRI) was performed on 1.5 T Siemens MR system. 3D T1 and T2 weighted images were acquired and processed to extract the white matter T2-lesion load. Results: 86 RRMS patients (86%) and 12 HCs (35.3%) were tested positive for the T. gondii IgG antibodies. This difference in IgG seropositivity between MS patients and HCs was statistically significant (p<0.05). On the other hand, 19 RRMS patients (19%) and 4 HCs (11.7%) were tested positive for the Toxoplasma gondii IgM antibodies, and this difference was statistically insignificant (p >0.05). Neither IgG nor IgM concentration levels showed any significant association (p >0.05) with MS disease’s indices. Conclusions: A strong significant association between the presence of anti-toxoplasma IgG antibodies and MS disease was found. Serum antibodies for T. gondii should be tested regularly among MS patients and anti-parasitic therapy should be provided, when necessary to prevent any reactivation and dissemination of the disease among these immunocompromised patients.